Response to drought of Zn-stressed Quercus suber L. seedlings - Disante, Karen B; Fuentes, David; Cortina, Jordi (Environmental and Experimental Botany, 2011)
Zinc is an essential nutrient for higher plants but it becomes toxic as its availability increases. In nature, different stress factors commonly occur concurrently, challenging our ability to predict their impacts. Information on zinc (Zn) effect on plant ability to withstand other sources of stress is scarce. This study examines the effect of zinc supply rate on the response of Quercus suber L. seedlings to water stress. Seedlings were treated with four levels of zinc from 3 to 150 M, and then exposed to a short severe drought. Zinc concentration in leaves and roots increased with zinc availability. Maximum photosynthetic rate, photochemical efﬁciency, root length and speciﬁc root length decreased as Zn availability increased. The decrease was particularly intense between 50 and 150 M Zn. The relative effects of drought were less intense in seedlings receiving higher doses of Zn than in those receiving 3 M. Thus, at severe drought, relative water content of detached leaves decreased to 52% in seedlings receiving the lowest level of Zn. In contrast, relative water content remained above 70% in seedlings exposed to high concentrations of this metal. The pattern was similar for photosynthetic rate and stomatal conductance, as the decrease in these variables resulting from severe drought was 100% and 90% in seedlings receiving 3 M and 65% and 56% in seedlings receiving the highest Zn dose. Our results suggest that morpho-physiological responses to zinc may foster water conservation strategies and alleviate the effects of drought in the short term, but they may impair seedling ability to root and grow in a longer term
Keywords: growth response; Heavy metal; Relative water content; water use efﬁciency

Nutritional Status of Mediterranean Trees Growing in a Contaminated and Remediated Area - Domínguez, MaríaT; Marañón, Teodoro; Murillo, JoséM; Schulin, Rainer; Robinson, BrettH (Water, Air, and Soil Pollution, 2010)
t Soil contamination may contribute to forest decline, by altering nutrient cycling and acquisition by plants. This may hamper the establishment of a woody plant cover in contaminated areas, thus limiting the success of a restoration program. We studied the nutritional status of planted saplings of Holm oak (Quercus ilex subsp. ballota (Desf.) Samp.), white poplar (Populus alba L.), and wild olive tree (Olea europaea var. sylvestris Brot.) in the Guadiamar Green Corridor (SW Spain) and compared it with established adult trees. Soils in this area were affected by a mine-spill in 1998 and a subsequent restoration program. The spill resulted in soil acidification, due to pyrite oxidation, and deposited high concentrations of some trace elements. In some sites, we detected a phosphorus deficiency in the leaves of Q. ilex and O. europaea saplings, as indicated by a high N:P ratio (>16). For O. europaea, soil contamination explained 40% of the variability in leaf P and was negatively related to chlorophyll content. Soil pH was a significant factor predicting the variability of several nutrients, including Mg, P, and S. The uptake of Mg and S by P. alba was greater in acidic soils. The monitoring of soil pH is recommended since long-term effects of soil acidification may negatively affect the nutritional status of the trees
The following values have no corresponding Zotero field: publisher: Springer Netherlands
Keywords: Heavy metal; Olea europaea; phosphorus; Populus alba; Quercus ilex; soil remediation; Tree nutrition

Trace element accumulation in woody plants of the Guadiamar Valley, SW Spain: a large-scale phytomanagement case study. - Domínguez, María T; Marañón, Teodoro; Murillo, José M; Schulin, Rainer; Robinson, Brett H (Environmental pollution (Barking, Essex : 1987), 2008)
Phytomanagement employs vegetation and soil amendments to reduce the environmental risk posed by contaminated sites. We investigated the distribution of trace elements in soils and woody plants from a large phytomanaged site, the Guadiamar Valley (SW Spain), 7 years after a mine spill, which contaminated the area in 1998. At spill-affected sites, topsoils (0-25 cm) had elevated concentrations of As (129 mg kg(-1)), Bi (1.64 mg kg(-1)), Cd (1.44 mg kg(-1)), Cu (115 mg kg(-1)), Pb (210 mg kg(-1)), Sb (13.8 mg kg(-1)), Tl (1.17 mg kg(-1)) and Zn (457 mg kg(-1)). Trace element concentrations in the studied species were, on average, within the normal ranges for higher plants. An exception was white poplar (Populus alba), which accumulated Cd and Zn in leaves up to 3 and 410 mg kg(-1) respectively. We discuss the results with regard to the phytomanagement of trace element contaminated sites.
Keywords: Bioaccumulation; biodegradation; Environmental; Environmental Monitoring; Environmental Monitoring: methods; Heavy; Heavy metal; Heavy: analysis; Mass spectrometry; metals; Mining; Olea; Olea europaea; Olea: chemistry; Phytoremediation; Plant Leaves; Plant Leaves: chemistry; Populus; Populus alba; Populus: chemistry; Quercus; Quercus ilex; Quercus: chemistry; Soil; Soil Pollutants; Soil Pollutants: analysis; Soil: analysis; Spain; Species Specificity

Trace element accumulation in woody plants of the Guadiamar Valley, SW Spain: a large-scale phytomanagement case study. - Domínguez, María T.; Marañón, Teodoro; Murillo, José M.; Schulin, Rainer; Robinson, Brett H. (Environmental pollution (Barking, Essex : 1987), 2008)
Phytomanagement employs vegetation and soil amendments to reduce the environmental risk posed by contaminated sites. We investigated the distribution of trace elements in soils and woody plants from a large phytomanaged site, the Guadiamar Valley (SW Spain), 7 years after a mine spill, which contaminated the area in 1998. At spill-affected sites, topsoils (0-25 cm) had elevated concentrations of As (129 mg kg(-1)), Bi (1.64 mg kg(-1)), Cd (1.44 mg kg(-1)), Cu (115 mg kg(-1)), Pb (210 mg kg(-1)), Sb (13.8 mg kg(-1)), Tl (1.17 mg kg(-1)) and Zn (457 mg kg(-1)). Trace element concentrations in the studied species were, on average, within the normal ranges for higher plants. An exception was white poplar (Populus alba), which accumulated Cd and Zn in leaves up to 3 and 410 mg kg(-1) respectively. We discuss the results with regard to the phytomanagement of trace element contaminated sites.
The following values have no corresponding Zotero field: accession-num: 17602809
Keywords: Bioaccumulation; biodegradation; Environmental; Environmental Monitoring; Environmental Monitoring: methods; Heavy; Heavy metal; Heavy: analysis; Mass spectrometry; metals; Mining; Olea; Olea europaea; Olea: chemistry; Phytoremediation; Plant Leaves; Plant Leaves: chemistry; Populus; Populus alba; Populus: chemistry; Quercus; Quercus ilex; Quercus: chemistry; Soil; Soil Pollutants; Soil Pollutants: analysis; Soil: analysis; Spain; Species Specificity